In vitro and in vivo Effects of Artesunate on Echinococcus granulosus Protoscoleces and Metacestodes - Wen L; Lv G; Zhao J; Lu S; Gong Y; Li Y; Zheng H; Chen B; Gao H; Tian C; Wang J (Dove Medical Press, 2020)
Limei Wen,1– 3,* Guodong Lv,2,4,* Jun Zhao,1,3,* Shuai Lu,1,3 Yuehong Gong,1,3 Yafen Li,2 Haiya Zheng,2 Bei Chen,1,3 Huijing Gao,1,3 Chunyan Tian,2 Jianhua Wang1,3 1Pharmaceutical Department, The First Affiliated Hospital of Xinjiang Medical University, Urumqi 830054, People’s Republic of China; 2College of Pharmacy, Xinjiang Medical University, Urumqi 830054, People’s Republic of China; 3State Key Laboratory of Pathogenesis, Prevention, Treatment of Central Asian High Incidence Diseases, Urumqi 830054, People’s Republic of China; 4Clinical Medical Research Institute, The First Affiliated Hospital of Xinjiang Medical University, Urumqi 830054, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianhua WangPharmaceutical Department, The First Affiliated Hospital of Xinjiang Medical University, No. 137 Liyushan South Road, Urumqi 830054, People’s Republic of ChinaEmail jhw716@sohu.comBackground: In this study, we aim to investigate the efficiency of artesunate (AS) on Echinococcus granulosus protoscoleces and metacestodes.Methods: For the in vitro assay, the eosin dye exclusion test and transmission electron microscope (TEM) were utilized to evaluate the effects of AS against protoscoleces (PSCs) from Echinococcus granulosus. In addition, mortality, ultrastructure change, reactive oxygen species (ROS) content and DNA damage were measured in order to explore the anti-echinococcosis mechanism of AS. For the in vivo assay, CE-infected mice were divided into model group, albendazole (ABZ) group (200 mg/kg), low AS (AS-L) group (50 mg/kg), moderate AS (AS-M) group (100 mg/kg), and high AS (AS-H) group (200 mg/kg). Upon 6 weeks oral administration, wet weight of cysts and the ultrastructural changes of cystic wall were utilized to evaluate the effects of AS on metacestodes. In addition, the liver biochemical parameters, tumor necrosis factor-α (TNF-α), glutathione/glutathione oxidized (GSH/GSSG) ratio in serum, and H2O2, total superoxide dismutase (T-SOD) in cyst fluid were detected.Results: Both in vivo and in vitro experiments showed that AS showed anti-parasitic effects on CE. The AS could elevate the ROS level in the PSCs, which then resulted in obvious DNA damages. AS could significantly improve the liver biochemical parameters in infected mice compared with the model group (P < 0.05). Compared with the model group, AS-M and AS-H decrease the TNF-α content (P < 0.05); AS-H group significantly decrease in the serum GSH/GSSG ratio (P < 0.05). The content of H2O2 in hydatid fluid treated by AS showed significant decrease compared with the model group (P < 0.01), while the T-SOD level showed significant elevation compared with model group (P < 0.01).Conclusion: In this study, we confirmed that the effects of AS on Echinococcus granulosus protoscoleces and metacestodes may be related to the DNA damages induced by oxidative stress, which provided solid information for the research and development of drugs for cystic echinococcosis.Keywords: cystic echinococcosis, artesunate, Echinococcus granulosus, reactive oxygen species, DNA damage